Pengembangan Gim TAP untuk Melatih Koordinasi Mata dan Tangan Berbasis Web untuk Remaja - Johanes; Paramesthi Windriyani (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this research is to produce a gim to practice hand and eye coordination. The method used to develop this gim is the Gim Development Life Cycle (GDLC) method and in the development process of making it using the Construct 2 gim engine. The final result of the study was a gim named TAP that could be accessed from either a computer or a mobile device. The tes results from 12 respondents were 16.7% said that TAP gims greatly helped improve the coordination of their eyes and hands, as many as 41.7% said their eye and hand coordination increased and the remaining 41.7% felt no increase but also did not say that there was no point at all